Circulating Tumor DNA Combining with Imaging Analysis for Lesion Detection of Langerhans Cell Histiocytosis in Children - Siying Liu; Yongbing Zhu; Yu Chen; Yaqin Wang; Dedong Zhang; Jiasi Zhang; Yao Wang; Ai Zhang; Qun Hu; Aiguo Liu (Children)
Background: The detection of mutations from circulating tumor DNA (ctDNA) represents a promising enrichment technique. In this retrospective study, the significance of ctDNA and imaging in Langerhans cell histiocytosis (LCH) monitoring was first examined, and the broader role of ctDNA in monitoring LCH was additionally explored. Methods: First, data visualization and survival analysis models were used to generalize the concordance between cfBRAFV600E molecular response and radiographic response on clinical outcomes. Next, the molecular response of cfBRAFV600E was observed from a dynamic perspective. A comparative analysis was then conducted between cfBRAFV600E and ltBRAFV600E status, examining their relationship to clinical manifestations and prognosis of LCH. Results: Eventually, 119 participants were enrolled in this trial between 2019 and 2023. Progression-free survival (PFS) was significantly shorter in patients with both radiologic and cfDNA molecular progression (17.67 versus 24.67 months, p < 0.05) compared to those without. A critical cfBRAFV600E value of 0.03% has been determined for the first time. Both cfBRAFV600E and ltBRAFV600E mutations were associated with a higher proportion of children under 3 years of age, skin and spleen involvement, and a lower 3-year PFS rate. In contrast to ltBRAFV600E, cfBRAFV600E was linked to a higher proportion of risk organ invasion LCH (52% vs. 27.9%, p < 0.05) and a better therapeutic response at the sixth week (24% vs. 4.7%, p < 0.05). Furthermore, in patients with risk organ invasion-LCH and multisystem-LCH subtypes, cfBRAFV600E was associated with a significantly lower 3-year PFS. Conclusions: In summary, these findings enhanced and supplemented the implications of ctDNA and imaging analysis application in children with LCH.